Hubungan Intensitas Media Sosial dengan Prestasi Belajar Fiqih di Madrasah Tsanawiyah - Lia Marlina (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
This study aims to examine the effect of social media use on student learning achievement in Fiqh subjects at MTsN 1 Pesawaran. The problem underlying this study is the tendency of students to spend more time on social media, thus ignoring their responsibilities in learning. This study uses a quantitative approach with a causal research type that aims to determine the cause and effect relationship between two variables. Data collection techniques are carried out through observation, interviews, questionnaires, and documentation. The data obtained are then analyzed using descriptive analysis and statistical analysis which include validity tests, reliability tests, and hypothesis tests. Hypothesis testing is carried out using simple linear regression analysis. The results of the study indicate that the use of social media by students is in the good and controlled category. However, the results of the statistical analysis show that there is no significant influence between the use of social media on student learning achievement in Fiqh subjects at MTsN 1 Pesawaran. Thus, it can be concluded that social media is not the main factor influencing student learning achievement in the context of Fiqh subjects at the madrasah.